Implementasi Kegiatan Pengabdian Masyarakat: Sosialisasi Stunting dan Pembuatan Nugget Ikan pada Masyarakat Desa Menceh Kecamatan Sakra Timur Kabupaten Lombok Timur - Azhahra, Rizka Dwi; Saputri, Ferza Ayu; Wahyudi, Khairil; Hafirah, Diyah Putri; Sugra, Agung; Zulfa, Ria; Herbianti, Fitri; Andewy, Asri; Rahman, Hardyanto; Ramadhan, Muhammad Wahyu; Zuhdi, Muhammad (Universitas Mataram, 2024)
Stunting and malnutrition are still serious problems in Indonesia. Integrated handling from various sectors is needed to reduce the number of stunting cases. Menceh Village, East Sakra Sub-district, East Lombok Regency, has a majority population of farmers and fishermen. Through Community Service (KKN) activities, we adopted the innovation of making fish nuggets as a local solution to improve nutritional status and reduce the risk of stunting. Counseling and demonstrations were conducted to improve community understanding and skills related to stunting and fish nugget making. The results showed participants' enthusiasm and increased understanding of nutrition and healthy practices.